Isolated levocardia with situs inversus without cardiac abnormality in fetus: prenatal diagnosis and management - Eriç Özdemir, Mucize; Demirci, Oya (Perinatal Medicine Foundation, 2020)
Objective Isolated levocardia is a situs abnormality that the heart is in the normal levo position, but the abdominal viscera are in dextro position. Most cases are accompanied by structural heart anomalies. In this case, we aimed to present a fetus with isolated levocardia without cardiac abnormality. Case(s) The mother was referred to our clinic with a suspicion of fetal dextrocardia at 22 weeks of gestation. When detailed examination was planned by ultrasonography isolated levocardia was detected in fetus. There were no cardiac abnormalities in fetal echocardiography. Fetus was followed up until delivery and newborn was examined again at postnatal period. No problem was detected until the age of 2 years. Conclusion Fetal situs should be assessed by ultrasonography in all pregnant women.